Ground-water potentialities in the Crescent Valley, Eureka and Lander Counties, Nevada. - Zones, C. P. (Christie Paul), 1926-; Geological Survey (U.S.); Nevada (U.S: G.P.O., Washington, D.C., 1961)
Landforms and drainage
Climate
In English
Pbk.
Keywords: Water--Analysis; Water-supply; Nevada--Crescent Valley